Optimizing Customer Engagement: Employing Triangulation Methodology to Improve Social Media Content Strategy for MSME - Lady, Lady; Shevia, Shevia; Nurjanah, Listia (Universitas Bunda Mulia, 2024)
The internet offers great potential for the development of micro, small, and medium enterprises (MSMEs) in Indonesia. Nisa Kitchen, an MSME in Batam City specializing in making brownies, utilizes digital marketing and social media to grow their business. This is a qualitative research study aimed at exploring the effect of engaging social media marketing content on customer engagement, with a focus on Nisa Kitchen. In this study, researchers use methodological triangulation to gather data from various sources and perspectives. This technique allows for the validation of findings by combining different research approaches such as content analysis, interviews, and observations, thereby producing a deeper and more accurate understanding of the topic under investigation. In addition to the owner, the primary participants in this study are customers who have made purchases from Nisa Kitchen and are above 17 years old. The study aims to gain a comprehensive understanding of the implications for Nisa Kitchen. One of the challenges faced by MSMEs is a lack of understanding of technology and social media. This study emphasizes its unique contribution to the literature by presenting new insights and a comprehensive approach to enhancing customer engagement through attractive marketing content on social media. The study proposes solutions by creating useful and engaging content using Canva, Linktree, and WhatsApp Business to simplify customer access to Nisa Kitchen. The research findings indicate positive changes in social media insight data (engagement) and customer interviews.